Cleft palate in HIV‐exposed newborns of mothers on highly active antiretroviral therapy. (11th September 2014) - Fasunla, A.J.; Ogunbosi, B.O.; Odaibo, G.N.; Taiwo, B.; Nwaorgu, O.G.B.; Olaleye, D.O.; Murphy, R.L.; Adewole, I.F.; Kanki, P.; Akinyinka, O.O.
Abstract: Cleft lip/palate, though rare, is the commonest head and neck congenital malformation. Both genetic and environmental factors have been implicated in the aetiopathogenesis, but the role of in utero exposure to human immunodeficiency virus (HIV) and highly active antiretroviral therapy (HAART) is still being investigated. This short communication reports the occurrence of cleft palate in three newborns exposed in utero to HIV and HAART. This is a case series of HIV‐exposed newborns observed to have cleft palate among a larger cohort of HIV‐exposed and HIV‐unexposed newborns in a study evaluating the effect of HIV infection and HAART on newborn hearing. The Risk Ratio (RR) was calculated to detect a potential association between in utero exposure to efavirenz (EFV)‐containing antiretroviral therapy and cleft palate. Three HIV‐exposed newborns with cleft palate were identified during hearing screening performed on 126 HIV‐exposed and 121 HIV‐unexposed newborns. Two had exposure to tenofovir + lamivudine + efavirenz (TDF + 3TC + EFV), whereas the third had exposure to zidovudine + lamivudine + nevirapine (ZDV + 3TC + NVP) during the first trimester. There was no statistically significant association between presence of cleft palate and exposure to an EFV containing HAART regimen [ P  = 0.07, RR = 10.95 (0.94–126.84)]. This communication highlights the possible aetiologic role of HAART in cleft palate, the need for further prospective follow‐up studies and establishment of antiretroviral pregnancy, birth and neonatal registries.